21-Hydroxylase-Specific CD8+ T Cells in Autoimmune Addison’s Disease Are Restricted by HLA-A2 and HLA-C7 Molecules - Hellesen, Alexander; Aslaksen, Sigrid; Breivik, Lars; Røyrvik, Ellen Christine; Bruserud, Øyvind; Edvardsen, Kine; Brokstad, Karl Albert; Wolff, Anette Susanne Bøe; Husebye, Eystein Sverre; Bratland, Eirik (Frontiers in Immunology, 2021)
Objectives: CD8+ T cells targeting 21-hydroxylase (21OH) are presumed to play a central role in the destruction of adrenocortical cells in autoimmune Addison’s disease (AAD). Earlier reports have suggested two immunodominant CD8+ T cell epitopes within 21OH: LLNATIAEV (21OH342-350), restricted by HLA-A2, and EPLARLEL (21OH431-438), restricted by HLA-B8. We aimed to characterize polyclonal CD8+ T cell responses to the proposed epitopes in a larger patient cohort with AAD. Methods: Recombinant fluorescent HLA-peptide multimer reagents were used to quantify antigen-specific CD8+ T cells by flow cytometry. Interferon-gamma (IFNγ) Elispot and biochemical assays were used to functionally investigate the 21OH-specific T cells, and to map the exactly defined epitopes of 21OH. Results: We found a significantly higher frequency of HLA-A2 restricted LLNATIAEV-specific cells in patients with AAD than in controls. These cells could also be expanded in vitro in an antigen specific manner and displayed a robust antigen-specific IFNγ production. In contrast, only negligible frequencies of EPLARLEL-specific T cells were detected in both patients and controls with limited IFNγ response. However, significant IFNγ production was observed in response to a longer peptide encompassing EPLARLEL, 21OH430-447, suggesting alternative dominant epitopes. Accordingly, we discovered that the slightly offset ARLELFVVL (21OH434-442) peptide is a novel dominant epitope restricted by HLA-C7 and not by HLA-B8 as initially postulated. Conclusion: We have identified two dominant 21OH epitopes targeted by CD8+ T cells in AAD, restricted by HLA-A2 and HLA-C7, respectively. To our knowledge, this is the first HLA-C7 restricted epitope described for an autoimmune disease.